Evaluation of E-Module Assisted Tai Cooperative Learning Model in Improving Student's Mathematics Literature (Universitas Negeri Semarang, 2022)
The purpose of this study was to evaluate, identify and categorize the level of mathematical literacy of class VII students at MTs Husnul Khotimah 2 Kuningan before and after the implementation of the Team Assisted Individualization (TAI) learning model assisted by e-modules. This research method is quantitative with One Group Pretest-Posttest design. The data collection technique used a mathematical literacy test for pretest and posttest with number content. While the data analysis technique used the average difference test (Paired Sample T-Test) and the Gain test. The results showed that based on the results of the average difference test, there were differences in scores before and after the application of the Team Assisted Individualization (TAI) model with the help of e-modules and the application of the TAI model could also improve mathematical literacy with an average score of each before and after the application of the model is 47.07 and 70.33 with categorization of improvement based on the Gain test after the application of the TAI model assisted by e-modules, namely 7 students of low improvement, 18 students of moderate improvement, and 5 students of high improvement and the average increase of students after the application of the model TAI assisted by e-module is 0.481 and is included in the moderate criteria. Thus, one way to improve students' mathematical literacy is to use the TAI learning model.